Nobody gives a #%&!: a factorial survey examining the effect of criminological evidence on opposition to sex offender residence restrictions - Rydberg, Jason (Journal of experimental criminology, 2018)
This short report tests whether altering messages concerning the presentation (i.e., criminal justice actor experience vs. summary of scientific findings) or nature of criminological research findings (i.e., lack of crime control effect vs. collateral consequences) regarding the (in)efficacy of sex offender residence restrictions (SORR) would subsequently affect public support for this policy.